Intensifikasi Tembakau Virginia Di Kabupaten Bojonegoro = Virginia Tobacco Intensification Program, a Case Study in Bojonegoro, East Java - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
The Virginia tobacco intensification (ITV) program in Bojonegoro had been carried out and financed by three sigarettes manufactures. The farmers who join t he program received credit facilities such as fertilizers, pesticides and the guarantee of the marketing of their product (tobacco leaves). The combination of TSP, ZA and ZK fertilizer used by ITV farmers is more profitable than the combination of TSP and urea. If TSP, ZA and ZK are combinned at optimum level it will increase farm income more than 17 percent. But combination of TSP and urea at optimum level only increase the farm income less than one percent. The ETV program provides several advantages i.e. supply of farm credit at low interest, good combination of fertilizer and higher price of the tobacco leaves.